The impact of lateral ankle ligament injuries on ankle stability and talar cartilage stress: a finite element analysis of combined injury mechanisms - Ji, Shuai; Sun, Liang; Wang, Qian; Qi, Hongfei; Wu, Bo; Du, Bing; Zhang, Chengcheng; Zhang, Kun; Li, Zhong; Li, Ming; Lu, Yao (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveTo investigate the differential biomechanical effects of injuries to the superior and inferior fascicles of the anterior talofibular ligament (ATFL) and the calcaneofibular ligament (CFL) on ankle stability and talar cartilage stress, providing a basis for the Fascicle-specific diagnosis and treatment of chronic ankle instability.MethodsA finite element model incorporating bones, articular cartilage, and nine sets of ligament spring elements was created based on CT data from the ankle of a 26-year-old male volunteer. Six conditions were simulated: 1. intact model; 2. superior ATFL Fascicle injury; 3. inferior ATFL Fascicle injury; 4. complete ATFL injury (superior + inferior Fascicles); 5. CFL injury; and 6. combined ATFL + CFL injury. Anterior drawer test (100 N anterior traction), varus stress test (1.7 N·m torque), and single-leg standing test (600 N axial load) were performed to measure talar displacement and cartilage stress distribution.Results1. In the anterior drawer test, talar displacement was greater in superior ATFL Fascicle injuries than in inferior ATFL Fascicle and CFL injuries. 2. In the inversion test, talar displacement was greater in CFL injuries than in superior, inferior, or complete ATFL injuries. 3. In the single-leg standing test, all five injury models altered the contact stress distribution on the talar cartilage compared to the intact model, shifting the peak stress from the anterolateral dome to the anteromedial dome and increasing pressure on the anteromedial talar dome. The peak stress magnitudes were ranked as follows: ATFL + CFL injury > complete ATFL injury > superior ATFL Fascicle injury > inferior ATFL Fascicle injury > CFL injury. 4. The combined ATFL + CFL injury model showed significantly greater displacement and peak stress than the other four injury models.ConclusionThe superior Fascicle of the ATFL is the primary restraint for anterior stability; the CFL dominates rotational stability; combined injuries trigger a biomechanical cascade failure; lateral ankle ligament injuries lead to increased contact stress on the anteromedial talar cartilage, contributing to the development of arthritis.